CAPITAL ASSET PRICING MODEL TESTING IN WEST AFRICA ECONOMIC AND MONETARY UNION STOCK MARKET: THE CASE OF IVORIAN LISTED FIRMS - Yannick Gahé, Zimy Samuel; Hongzhong, Zhao; Allate, Brou Matthias; Belinga, Thierry (International Journal of Research -GRANTHAALAYAH, 2017)
This paper investigates the validity of Capital Asset Pricing Model (CAPM) for the West African Economic and Monetary Union (WAEMU) stock market using monthly stock returns of twenty Côte d’Ivoire’s listed firms from January 2002 to December 2011. We split this interval into different time periods. Each one of them has also been divided into two different sub-periods among which one served as estimation mean and the second one helped to test the estimated parameters obtained using a times series regression. Afterwards some statistical tests have been conducted to see whether the CAPM’s hypotheses hold or not. The findings showed that higher risk is not associated with higher level of return within the study area. Also, there was no relation between stock return and non-systemic risk except for one period where we found evidence that stock returns were affected by other risk than the systematic risk. On the contrary the stock expected rate of return had a linear relationship with the systematic risk. The study suggested that the listed companies consider other factors and variables which could explain their returns.